THEORY OF KHUDI AND SPIRITUAL DEVELOPMENT ON IQBAL’S PERSPECTIVE: Analysis Spiritual Strengthening Islamic Perspective - Arroisi, Jarman; Assakhyyu Qorib, Khoffifa (TAJDID: Jurnal Ilmu Ushuluddin, 2023)
Nowadays most people lack their self-control, which can result in sadness, stress corruption, even murder and suicide The purpose of writing this paper is to find out Muhammad Iqbal's theory of khudi. By descriptive analysis method, this paper concludes that: First, Muhammad Iqbal's theory of khudi as a strengthening of spirituality in Islamic psychology. Second, khudi is defined as soul, individual, and personality. Third, the factors to strengthen khudi include: love, faqr, toleration, courage, and action. Fourth, the three main stages to strengthen the spirituality of khudi include: obedience to Allah's law, self-control, and Caliphate. Fifth, Insan Kamil is a form of realization of the value of spirituality in khudi as an understanding of human nature as a servant of Allah to become the Caliph of Allah on earth Di era modern sebagian besar manusia kehilangan self-control yang menyebabkan depresi, stres, korupsi, bahkan pembunuhan dan aksi bunuh diri.  Tujuan penulisan makalah ini untuk mengetahui teori khudi Muhammad Iqbal. Dengan menggunakan metode descriptive analisis makalah ini menghasilkan kesimpulan bahwa: Pertama, teori khudi Muhammad Iqbal sebagai penguatan spiritualitas dalam psikologi Islam. Kedua, khudi diartikan sebagai jiwa, individual, dan kepribadian. Ketiga, faktor untuk memperkuat khudi diantarannya: cinta, faqr, tolerasi, keberanian, dan tindakan. Keempat, tiga tahap utama untuk memperkuat spiritualitas khudi diantaranya: ketaatan akan hukum Allah, pengendalian diri, dan ke-Khalifahan. Kelima, insan Kamil adalah bentuk terealisasinya nilai spiritualitas dalam khudi sebagai pemahaman hakikat manusia sebagai hamba Allah hingga menjadi Khalifah Allah di muka bumi.